1998
DOI: 10.1046/j.1365-2443.1998.00174.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of receptors and Smad proteins involved in activin signalling in a human epidermal keratinocyte cell line

Abstract: Background: Activin A is a multifunctional protein, which is a member of the transforming growth factor-b (TGF-b) superfamily. Smad proteins have recently been shown to transduce signals for the TGF-b superfamily of proteins, and Smad2 was implicated in activin signalling in Xenopus embryos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 59 publications
2
45
1
3
Order By: Relevance
“…This was confirmed by our recent results, which demonstrated that activin receptor signaling in keratinocytes is important for hair follicle morphogenesis and wound re-epithelialization (Bamberger et al, 2005). In addition, a role of activin in the regulation of keratinocyte proliferation and differentiation was found in in vitro studies with keratinocyte monocultures, where a weak inhibitory effect of activin on keratinocyte proliferation and induction of keratinocyte differentiation by this factor was demonstrated (Shimizu et al, 1998;Seishima et al, 1999). In addition, activin was shown to stimulate keratinocyte migration (Zhang et al, 2005).…”
supporting
confidence: 78%
See 1 more Smart Citation
“…This was confirmed by our recent results, which demonstrated that activin receptor signaling in keratinocytes is important for hair follicle morphogenesis and wound re-epithelialization (Bamberger et al, 2005). In addition, a role of activin in the regulation of keratinocyte proliferation and differentiation was found in in vitro studies with keratinocyte monocultures, where a weak inhibitory effect of activin on keratinocyte proliferation and induction of keratinocyte differentiation by this factor was demonstrated (Shimizu et al, 1998;Seishima et al, 1999). In addition, activin was shown to stimulate keratinocyte migration (Zhang et al, 2005).…”
supporting
confidence: 78%
“…Similar to TGF-b, activin has opposite effects on keratinocytes and fibroblasts. It slightly reduces keratinocyte proliferation (Shimizu et al, 1998;Seishima et al, 1999), but enhances growth of cultured fibroblasts (Ohga et al, 1996;Yamashita et al, 2004). The different responses of fibroblasts and keratinocytes to activin and TGF-b are reflected by the opposite regulation of Id expression in both cell types, suggesting that the up-or downregulation of Id proteins by activin/TGF-b could mediate -at least in part -the effects of these factors on proliferation of fibroblasts and keratinocytes.…”
Section: Id Proteins In Epidermal Homeostasismentioning
confidence: 99%
“…Recent studies from us and from others have revealed a novel role of the TGF-b superfamily member activin in the regulation of keratinocyte proliferation and di erentiation (Shimizu et al, 1998;Seishima et al, 1999;Munz et al, 1999). Interestingly, the e ects of activin on keratinocytes seem to di er from those of Figure 7 Expression of mxi1/mad2, mad3, mad4, mnt/rox, c-myc and mmip1 mRNAs in normal and wounded skin.…”
Section: Discussionmentioning
confidence: 98%
“…A picture of the RNA gel is shown below the RNase protection assays. The same set of RNAs was used for the RNase protection assays shown here and in Figure 5 TGF-b, since the latter caused a much stronger inhibition of keratinocyte proliferation in vitro compared to activin (Shimizu et al, 1998;Seishima et al, 1999). In vivo, the di erences were even more striking, since targeted expression of TGF-b1 in the epidermis of transgenic mice caused severe inhibition of keratinocyte proliferation (Sellheyer et al, 1993, Wang et al, 1999.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation